Parents’ planning, children’s agency and heritage language education: Re-storying the language experiences of three Chinese immigrant families in Australia - Shen, Chunxuan; Jiang, Wenying (Frontiers in Psychology, 2023)
This study delves into the heritage language experiences of Australian-born Chinese immigrant children under the framework of family language policy. Storytelling as a narrative inquiry method is used to reveal the lived experiences of the protagonists in relation to heritage language and culture. The three family stories involved for case studies reveal different levels of parent agency in Chinese immigrant families regarding their children’s home language use and heritage language education. It is noted that the level of child agency corresponds with the level of their parent agency. Where parents strongly advocate and practice heritage language maintenance, stronger agency is observed in their children to continue the use and learning of their heritage language. In addition, maintaining harmony while parents are implementing family language policies and providing children with formal instruction in heritage language is conducive to heritage language development, particularly in terms of its literacy.